2023
DOI: 10.1680/jwama.20.00040
|View full text |Cite
|
Sign up to set email alerts
|

Flow patterns and free-surface dynamics in hydraulic jump on pebbled rough bed

Abstract: Some basic characteristics of a classic hydraulic jump flow over a pebbled rough bed, as well as on a smooth bed as a reference, are presented in this experimental study. For the experiments, an inflow Froude number Fr1 from 1.54 to 4.94 and inflow Reynolds number Re1 from 42 000 to 230 000 were considered. Visual observations and measurements suggested some differences between the formation of a hydraulic jump on rough and smooth bed configurations, including different air entrainment processes, larger vortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Some studies have conducted velocity measurements in turbulent flows but employed high time intervals. For instance, [3,19,20] worked with point measurements of the discharge, capturing only a single point per assessed event and not tracking the rising and falling phases of the hydrograph. These intervals may surpass the time scale of the velocity fluctuations, potentially losing crucial information about the flow turbulence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have conducted velocity measurements in turbulent flows but employed high time intervals. For instance, [3,19,20] worked with point measurements of the discharge, capturing only a single point per assessed event and not tracking the rising and falling phases of the hydrograph. These intervals may surpass the time scale of the velocity fluctuations, potentially losing crucial information about the flow turbulence.…”
Section: Discussionmentioning
confidence: 99%
“…This article represents a significant contribution to hydrodynamic modeling, as few studies effectively measure flow variables in conjunction with the water level using a highfrequency sampling rate capable of capturing changes in the flow. Typically, measurements are taken at discrete intervals [3,19,20]. Other studies consider only continuous water level measurements, inferring flow from this approach [1,14].…”
Section: Introductionmentioning
confidence: 99%
“…Trapezoidal open channels are commonly used to transport water in irrigation systems, drainage ditches, and stormwater management systems [14,15]. Wanoschek et al [16] studied symmetrical trapezoidal channels and Rodriguez-Diaz [17] studied asymmetrical trapezoidal channels.…”
Section: Introductionmentioning
confidence: 99%
“…Bahmanpouri et al. (2021) investigated the unsteady flow motions developing on a pebble bed and observed larger internal vortical structures, stronger backward flow, and an enhanced jump toe oscillation range but reduced free‐surface fluctuations. No hydraulic jump interaction with perturbing vegetation roughness has been investigated, neither for the effects of flexibility nor porosity of larger‐sized plant elements.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the efforts on three-dimensional velocity field and bottom stress characterization, detailed air-water flow measurements were rare in rough-bed hydraulic jumps until Felder and Chanson (2018) who used a phase-detection probe as a similar approach to the previous classic hydraulic jump investigations. Bahmanpouri et al (2021) investigated the unsteady flow motions developing on a pebble bed and observed larger internal vortical structures, stronger backward flow, and an enhanced jump toe oscillation range but reduced free-surface fluctuations. No hydraulic jump interaction with perturbing vegetation roughness has been investigated, neither for the effects of flexibility nor porosity of larger-sized plant elements.…”
mentioning
confidence: 99%